2008
DOI: 10.1017/s0954102008001557
|View full text |Cite
|
Sign up to set email alerts
|

Adult male southern elephant seals from King George Island utilize the Weddell Sea

Abstract: Adult male southern elephant seals instrumented in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 52 publications
(79 reference statements)
2
38
2
Order By: Relevance
“…If we consider that: (a) The juvenile seals sampled in the present study belong to the southernmost breeding population of M. leonina; (b) studies of movements at sea by satellite tellemetry of juvenile seals from this colony had shown that most of them travelled to the southwest of the South Shetland islands and centred their foraging activities in ice free areas west of the Antarctic peninsula (Bornemann et al, 2000;toSh et al, 2009). Then, the almost exclusively Antarctic distribution of their cephalopod prey taxa is probably a refl ection of their foraging areas and not a bias from the sampling technique.…”
Section: Lrl/lhlmentioning
confidence: 99%
See 1 more Smart Citation
“…If we consider that: (a) The juvenile seals sampled in the present study belong to the southernmost breeding population of M. leonina; (b) studies of movements at sea by satellite tellemetry of juvenile seals from this colony had shown that most of them travelled to the southwest of the South Shetland islands and centred their foraging activities in ice free areas west of the Antarctic peninsula (Bornemann et al, 2000;toSh et al, 2009). Then, the almost exclusively Antarctic distribution of their cephalopod prey taxa is probably a refl ection of their foraging areas and not a bias from the sampling technique.…”
Section: Lrl/lhlmentioning
confidence: 99%
“…25 de Mayo population of M. leonina, studies have reported that juveniles (in their first year of life), females and adult males develop their foraging activity in different areas of the Southern Ocean (Bornemann et al, 2000;toSh et al, 2009). Additionally, dietary studies conducted to date on this population, have shown that its diet differs from those of other colonies since it is mainly represented by fish and squid species distributed almost entirely south of the Antarctic Polar Front (daneri et al, 2000daneri & carlini, 2002;PiatkowSki et al, 2002).…”
mentioning
confidence: 98%
“…This individual was later excluded from analysis due to a lack of dive related data. Detailed data related to the movements of the various animals included in this study are discussed elsewhere (Tosh et al 2009;Tosh 2010). Only data resulting from devices that recorded most, if not all of the dive parameters for a period in excess of 30 days were analysed to ensure adequate representation of overall dive behaviour resulting in data sets of nine and four animals from King George Island and Marion Island respectively (Table 1).…”
Section: Instrumentationmentioning
confidence: 99%
“…During their time spent at sea, elephant seals migrate long distances (up to 5,000 km) and dive to great depths, frequenting depths between ca. 400 and 900 m and sometimes even depths deeper than 2,000 m (Campagna et al 1995;Malherbe 1998;Field et al 2001;Muelbert et al 2004;Tosh et al 2009;McIntyre et al 2010a). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation